Disability subtypes and mortality rates in older adults: A longitudinal population-based study (NEDICES). (January 2019) - Contador, Israel; Bermejo-Pareja, Félix; Fernández-Calvo, Bernardino; LLamas, Sara; Villarejo, Alberto; Vega, Saturio; Benito-León, J.
Highlights: A combined assessment of functional disabilities based on health conditions and IADL may increase the predictive validity for mortality in older adults. Functional limitations based on SFL or IADL are associated with diverse explanatory factors, which underline the importance of item contents to explain different mortality risks for each disability subtype. Prompt detection of functional disabilities may help to implement multi-factorials interventions for prevention of earlier mortality in older adults. Abstract: Objective: We investigated the mortality rates of three subtypes of disability and their specific explanatory factors in older adults. Methods: Our data come from NEDICES, a population-based longitudinal cohort study of Spanish older adults. We examined 3816 participants without dementia who completed the Pfeffer's Functional Activities Questionnaire (FAQ) and an assessment of self-perceived functional limitations (SFL) associated with health conditions. Subjects were classified into mutually exclusive subtypes of disability: subtype 1 (SFL), subtype 2 (impaired FAQ), and subtype 3 (impaired FAQ plus SFL). Factors related to all disability subtypes were analyzed using a multinomial logistic regression (MLR), whereas Cox regression (CR) models adjusted by covariates were applied to compare survival rates between groups at the 5-year follow up. Results: The CR models indicated that SFL and FAQ scores were associated with higher risk of mortality at 5-years. After stratifying by subtypes of disability, mortality was significantly higher in subtype 3 than in subtypes 1 and 2. All models were consistent after adjusting by different covariates. The MLR showed that subtype 1 was specifically associated with the number of comorbidities, whereas subtype 2 was associated with lower MMSE scores depression and living in nursing homes. Conclusions: Our results show that the combination of impaired FAQ plus SFL have an increased differential predictive utility for mortality than approaches based on unique measures. They also indicate that both measures of disability are associated with different explanatory factors.